Temporal trends of legacy organochlorines in different white-tailed eagle (Haliaeetus albicilla) subpopulations: A retrospective investigation using archived feathers. (May 2020) - Sun, Jiachen; Covaci, Adrian; Bustnes, Jan Ove; Jaspers, Veerle L.B.; Helander, Björn; Bårdsen, Bård-Jørgen; Boertmann, David; Dietz, Rune; Labansen, Aili Lage; Lepoint, Gilles; Schulz, Ralf; Malarvannan, Govindan; et al.
Graphical abstract: Highlights: Spatiotemporal trends of legacy OCs were reconstructed using white-tailed eagle feathers. Concentrations of PCBs, DDTs and HCHs were distinctively higher in Sweden. Concentrations of CHLs and HCB were distinctively higher in Greenland. Significant decreasing trends were observed for most OCs in the three subpopulations. PCBs did not show a significant decreasing trend (1985–2013) in the Greenland subpopulation. Abstract: Understanding the spatiotemporal patterns of legacy organochlorines (OCs) is often difficult because monitoring practices differ among studies, fragmented study periods, and unaccounted confounding by ecological variables. We therefore reconstructed long-term (1939–2015) and large-scale (West Greenland, Norway, and central Sweden) trends of major legacy OCs using white-tailed eagle ( Haliaeetus albicilla ) body feathers, to understand the exposure dynamics in regions with different contamination sources and concentrations, as well as the effectiveness of legislations. We included dietary proxies ( δ 13 C and δ 15 N) in temporal trend models to control for potential dietary plasticity. Consistent with the hypothesised high local pollution sources, levels of polychlorinated biphenyls (PCBs), dichlorodiphenyltrichloroethanes (DDTs) and hexachlorocyclohexanes (HCHs) in the Swedish subpopulation exceeded those in the other subpopulations. In contrast, chlordanes (CHLs) and hexachlorobenzene (HCB) showed higher concentrations in Greenland, suggesting the importance of long-range transport. The models showed significantly decreasing trends for all OCs in Sweden in 1968–2011 except for CHLs, which only decreased since the 1980s. Nevertheless, median concentrations of DDTs and PCBs remained elevated in the Swedish subpopulation throughout the 1970s, suggesting that the decreases only commenced after the implementation of regulations during the 1970s. We observed significant trends of increasing concentrations of PCBs, CHLs and HCB in Norway from the 1930s to the 1970s/1980s and decreasing concentrations thereafter. All OC concentrations, except those of PCBs were generally significantly decreasing in the Greenland subpopulation in 1985-2013. All three subpopulations showed generally increasing proportions of the more persistent compounds (CB 153, p.p ′-DDE and β -HCH) and decreasing proportions of the less persistent ones (CB 52, p.p ′-DDT, α - and γ -HCH). Declining trends of OC concentrations may imply the decreasing influence of legacy OCs in these subpopulations. Finally, our results demonstrate the usefulness of archived museum feathers in retrospective monitoring of spatiotemporal trends of legacy OCs using birds of prey as sentinels.